Complexity-Based Triaging and Scheduling for Reducing Clinic Wait Times in Student-Run Free Clinics - Bu, Jennifer; Chung, Min Kyung; Xing, Kun; Ruben, Claire; Elver, Ashlie (Journal of Student-Run Clinics, 2023)
Student-run free clinics are a valuable resource for both patients who lack access to care and undergraduate medical education. Free clinics often face specific challenges, such as long clinic wait times, necessitating the development of strategies to minimize wait time and enhance patient satisfaction. We propose the use of a patient complexity score to facilitate patient scheduling and the proper assignment of students to complex patients based on training level. A numeric score estimating the complexity of each patient may provide valuable information to clinic organizers and ultimately reduce patient wait times.